-(x-7)=11

Simple and best practice solution for -(x-7)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x-7)=11 equation:



-(x-7)=11
We move all terms to the left:
-(x-7)-(11)=0
We get rid of parentheses
-x+7-11=0
We add all the numbers together, and all the variables
-1x-4=0
We move all terms containing x to the left, all other terms to the right
-x=4
x=4/-1
x=-4

See similar equations:

| 3x+7-5x=-13 | | y/3y=48 | | 1-3x=1-x | | (2b-6)/6=2/3 | | 5x-3(x-4)=-6+5-6 | | 8.52-11.8b=-18.4b-8.91 | | 7x–2=x–14 | | 2(4x−3)=4x−30 | | 8z-3(2z-4)=3(z-6) | | 3(5x-5)+2=7x+11 | | 8(2w-3)-w=3(3w+2) | | 13+5x-2x=3 | | 1-2x+24x=2x+7x+49 | | 3x+4(x-17)=12 | | -3-10z=-17-16-8z | | 9x+4=-6+2x+24 | | 6n=–8+5n | | 5x-22=-2x-7 | | -4(3p+5)+8p=-11 | | x/2+3=-10/2 | | 3x+4(x-17)=-12 | | 9x+11+3x=47 | | 3f+20=-19+16f | | 7k-3.2k=15.2 | | 9-10z=129 | | 2x+12+2x+5=180 | | 3(5x-5)=7x+11 | | 18k-12=12k | | -6x-25=3+11 | | c(-13)-3=-33 | | 49-3x=7 | | 14a-7=7 |

Equations solver categories